Polyene Phosphatidylcholine Ameliorates High Fat Diet-Induced Non-alcoholic Fatty Liver Disease via Remodeling Metabolism and Inflammation - Lu, Yang; Feng, Tingting; Zhao, Jinxiu; Jiang, Pengfei; Xu, Daxiang; Zhou, Menglu; Dai, Mengyu; Wu, Jiacheng; Sun, Fenfen; Yang, Xiaoying; Lin, Qisi; Pan, Wei (Frontiers in Physiology, 2022)
Recent years have witnessed a rise in the morbidity of non-alcoholic fatty liver disease (NAFLD), in line with the global outbreak of obesity. However, effective intervention strategy against NAFLD is still unavailable. The present study sought to investigate the effect and mechanism of polyene phosphatidylcholine (PPC), a classic hepatoprotective drug, on NAFLD induced by high fat diet (HFD). We found that PPC intervention reduced the mass of liver, subcutaneous, epididymal, and brown fats in HFD mice. Furthermore, PPC supplementation significantly mitigated liver steatosis and improved glucose tolerance and insulin sensitivity in HFD mice, which was accompanied by declined levels of hepatic triglyceride, serum triglyceride, low density lipoprotein, aspartate aminotransferase, and alanine aminotransferase. Using transcriptome analysis, there were 1,789 differentially expressed genes (| fold change | ≥ 2, P < 0.05) including 893 upregulated genes and 896 downregulated genes in the HFD group compared to LC group. A total of 1,114 upregulated genes and 1,337 downregulated genes in HFD + PPC group were identified in comparison to HFD group. With the help of Gene Ontology (GO) analysis, these differentially expressed genes between HFD+PPC and HFD group were discovered related to “lipid metabolic process (GO: 0006629),” “lipid modification (GO: 0030258),” and “lipid homeostasis (GO: 0055088)”. Though Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, we found pathways associated with hepatic homeostasis of metabolism and inflammation. Notably, the pathway “Non-alcoholic fatty liver disease (mmu04932)” (P-value = 0.00698) was authenticated in the study, which may inspire the potential mechanism of PPC to ameliorate NAFLD. The study also found that lipolysis, fatty acid oxidation, and lipid export associated genes were upregulated, while the genes in uptake of lipids and cholesterol synthesis were downregulated in the liver of HFD mice after PPC supplementation. Interestingly, PPC attenuated the metabolic inflammation via inhibiting pro-inflammatory macrophage in the livers of mice fed by HFD. In summary, this study demonstrates that PPC can ameliorate HFD-induced liver steatosis via reprogramming metabolic and inflammatory processes, which inspire clues for further clarifying the intervention mechanism of PPC against NAFLD.